PENAMBAHAN GUM ARABTERHADAP MUTU SIRUP KULIT DAN BUAH NANAS (Ananas comosus LMerr.) - Jumansyah, Hadi; Johan, Vonny Setiaries; Rahmayuni, Rahmayuni (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
ABSTRACTThe purpose of this research was to determine the best concentration of gum arabic in prevented sedimentation in syrup made frompeel and flesh of pineapple(Ananas comosus L Merr.).This researchusedCompletely Randomized Design (CRD) with six treatments and three replications followed by DNMRT test at 5% level. The treatments in this research were G0 (without addition of gumarabic), G1 (addition of gum arabic 0.01%), G2 (addition of gum arabic 0.02%), G3 (addition of gum arabic 0.03%), G4 (addition of gum arabic 0.04%), andG5(addition of gum arabic 0.05%). The result of analysis of variance showed that addition of gum arabic has significantly affected the pH, viscosity, sucrose, sedimentation, and sensory value on descriptive and hedonic attribute of taste and level of condensed, but did not significantly affected the flavour and colour. The best treatment in this research was G5 (additional of gum arabic 0.05%) with pH 5.13, viscosity 223.75 cP, sucrose 69.15%, sedimentation 7.23%, yellow colour, pineaple fruit flavour, sweetness and condensed. Keyword : syrup, pineapple, gum arabic